Pengaruh Strategi Pembelajaran Berdiferensiasi Terhadap Hasil Belajar Peserta Didik SMA Negeri 1 Lahusa - Indah Septa Ayu Laia; Parlindungan Sitorus; Mariana Surbakti; Eka Notasya Simanullang; Riossally Marselina Tumanggor; Bajongga Silaban (Jurnal Ilmiah Wahana Pendidikan, 2022)
Educators as managers of learning activities are expected to be able to create an effective, active learning atmosphere and meet the learning needs of students. The problems found by researchers when conducting observations were that the teaching and learning atmosphere still seemed passive and the teacher did not consider the learning needs of students. Based on the problems encountered, the researcher offers a solution, namely by applying a differentiated learning strategy. Researchers conducted research with the aim of looking at the effect of differentiated learning strategies on learning outcomes obtained by students of class X MIA SMA Negeri 1 Lahusa in the 2021/2022 school year. The research method used is nonequivalent control group design. The results of the right-tail t-test hypothesis test obtained the value of tcount > ttable , namely 2.381 > 2.014 with = 0.05, based on the testing criteria, the accepted hypothesis is Ha means that there is an effect of treatment of differentiated learning strategies on student learning outcomes SMA Negeri 1 Lahusa for the academic year 2021/2022.